Endoscopy Reporting Standards. (2013) - Beaulieu, Daphnée; Barkun, Alan N; Dubé, Catherine; Tinmouth, Jill; Hallé, Pierre; Martel, Myriam
Abstract : OBJECTIVES: The Canadian Association of Gastroenterology (CAG) recently published consensus recommendations for safety and quality indicators in digestive endoscopy. The present article focuses specifically on the identification of key elements that should be found in all electronic endoscopy reports detailing recommendations adopted by the CAG consensus group. METHODS: A committee of nine individuals steered the CAG Safety and Quality Indicators in Endoscopy Consensus Group, which had a total membership of 35 voting individuals with knowledge on the subject relating to endoscopic services. A comprehensive literature search was performed with regard to the key elements that should be found in an electronic endoscopy report. A task force reviewed all published, full-text, adult and human studies in French or English. RESULTS: Components to be entered into the standardized report include identification of procedure, timing, procedural personnel, patient demographics and history, indication(s) for procedure, comorbidities, type of bowel preparation, consent for the procedure, pre-endoscopic administration of medications, type and dose of sedation used, extent and completeness of examination, quality of bowel preparation, relevant findings and pertinent negatives, adverse events and resulting interventions, patient comfort, diagnoses, endoscopic interventions performed, details of pathology specimens, details of follow-up arrangements, appended pathology report(s) and, when available, management recommendations. Summary information should be provided to the patient or family. CONCLUSION: Continuous quality improvement should be the responsibility of every endoscopist and endoscopy facility to ensure improved patient care. Appropriate documentation of endoscopic procedures is a critical component of such activities.